Eutanasia e suicidio assistito. L’accertamento della capacità nei pazienti malati di demenza e disturbi mentali. (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
: In accordance with the legislations concerning the end-of-life situations currently in force, the patient's mental capacity to make the request is an essential requirement for the legitimacy of the euthanasia and assisted suicide (EAS) demand. Therefore, the patient should be able to make a free and well-considered request. This article deepens the procedures for mental capacity assessment in patients suffering from dementia and mental disorders, who required access to EAS. In any case, the presence of mental disorder does not compromise the mental capacity automatically. The number of EAS performed against dementia patients and mental illness sufferers, while being very low compared EAS performed against cancer patients, is slightly but continuously increasing. In this context, to avoid the slippery slope, the role of the psychiatrist becomes essential in verifying that the EAS request made by these patients is not the expression of the disease. While the law draws the legislative framework, through the identification of the parameters necessary for a legitimate EAS request, it’s the doctor, in his knowledge and belief, who has the competence to check the presence of these parameters in the patients.
Keywords: Euthanasia; physician assisted suicide; mental capacity; mental capacity in dementia patients; mental capacity in mental illness sufferers